2019
DOI: 10.1113/jp277450
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down or bottom up: decreased stimulus salience increases responses to predictable stimuli of auditory thalamic neurons

Abstract: Key pointsr Temporal imprecision leads to deficits in the comprehension of signals in cluttered acoustic environments, and the elderly are shown to use cognitive resources to disambiguate these signals.r To mimic ageing in young rats, we delivered sound signals that are temporally degraded, which led to temporally imprecise neural codes.r Instead of adaptation to repeated stimuli, with degraded signals, there was a relative increase in firing rates, similar to that seen in aged rats.r We interpret this increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 145 publications
4
26
0
Order By: Relevance
“…However, since increased excitability usually leads to decreased timing fidelity, which was not the case in the older medial MGB neurons, it is possible the alterations in temporal acuity and firing rate could arise due to an interaction between general decreases in tonic inhibition and changes in the extracellular matrix at the level of the auditory thalamus (see section below). Alternatively, such changes could arise as a result of alterations in the corticothalamic feedback loops as suggested by the observation that MGB firing rates to degraded stimuli increase over repeated presentations (Kommajosyula, Cai, Bartlett, & Caspary, 2019). The age-related changes in the medial MGB are of particular interest as the medial MGB is thought to act as a polysensory, integrative center, combining information across auditory and non-auditory areas (see Rouiller (1997) and Winer (1992) for review).…”
Section: The Aged Auditory Thalamus Actively Transforms Temporally mentioning
confidence: 99%
“…However, since increased excitability usually leads to decreased timing fidelity, which was not the case in the older medial MGB neurons, it is possible the alterations in temporal acuity and firing rate could arise due to an interaction between general decreases in tonic inhibition and changes in the extracellular matrix at the level of the auditory thalamus (see section below). Alternatively, such changes could arise as a result of alterations in the corticothalamic feedback loops as suggested by the observation that MGB firing rates to degraded stimuli increase over repeated presentations (Kommajosyula, Cai, Bartlett, & Caspary, 2019). The age-related changes in the medial MGB are of particular interest as the medial MGB is thought to act as a polysensory, integrative center, combining information across auditory and non-auditory areas (see Rouiller (1997) and Winer (1992) for review).…”
Section: The Aged Auditory Thalamus Actively Transforms Temporally mentioning
confidence: 99%
“…Descending inputs from AC and RTN are less likely to show the sharpening of temporal tunings as the interaction of excitatory postsynaptic potential and inhibitory postsynaptic potential because Kv4.2 is less associated with these inputs. It has been shown that the interaction of top-down and bottom-up inputs was important for predicting the temporal structures of sound in MGB neurons ( Kommajosyula et al, 2019 ). The authors used salient (100% amplitude modulation) and less salient (25% amplitude modulation) sound sequences that were predictable or random order.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus receives sensory information from the lower brainstem centers and modulates and sends this information to the cortex ( Sherman and Guillery, 2002 ). Thus, the MGB relays neural information of the sound to the auditory cortex (AC) and segregates speech signals into different patterns for comprehension of the conveyed messages, interpretation of emotions associated with speech, and identification of the individual speaking ( Dagnino-Subiabre et al, 2009 ; Bartlett, 2013 ; Chen et al, 2019 ; Kommajosyula et al, 2019 ; Mihai et al, 2019 ). In the auditory information processing, such as in language interpretation, high timing resolution is important ( Dagnino-Subiabre et al, 2009 ), and bottom-up inputs from the inferior colliculus (IC) preserve temporal information of sound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the repetition enhancement described in human studies differs drastically on spatial and temporal scales from the phenomenon described here, we find that it similarly involves a sequential enhancement in the response to subsequent presentations of the standard (Figure 6C, 8D). Repetition enhancement has also been observed in the medial geniculate body in response to temporally degraded stimuli that are hypothesized to engage top-down resources to compensate for bottom-up acoustic information loss (Cai et al, 2016;Kommajosyula et al, 2019). Interestingly, this enhancement is reversed when cortico-thalamic pathways are blocked, further suggesting that repetition enhancement in the auditory system reflects a top-down phenomenon (Kommajosyula et al, 2021).…”
Section: Repetition Enhancement and Repetition Suppression In Icmentioning
confidence: 99%